David Emmanuel Singh (ed.), Jesus and the Resurrection: Reflections of Christians from Islamic Contexts (Oxford: Regnum Studies in Global Christianity, 2014) - Maria Pia Paganelli (Nordicum-Mediterraneum, 2015)
A review of the following book: Jesus and the Resurrection: Reflections of Christians from Islamic Contexts. Edited by David Emmanuel Singh. Regnum Studies in Global Christianity. Oxford. 2014. PP. viii+195